Vibration of lightweight steel floor systems with occupants: Modelling, formulation and dynamic properties. (15th September 2017) - Zhang, Sigong; Xu, Lei; Qin, Jingwei
Highlights: A damped plate-oscillator model for coupled floor-occupant systems is proposed for floor vibration. The dynamic properties obtained from the proposed model are compared with the test results. Human-structure interaction on vibration of lightweight steel floors is investigated with various human models. Discussions on the human induced vibration of lightweight steel floors are presented. Abstract: Theoretical analyses are presented for investigating the vibration of lightweight steel floor systems with human occupants. A damped plate-oscillator model is proposed to obtain the dynamic properties of coupled floor-occupant systems. A generalized formulation of the damped plate-oscillator model is proposed. A complex eigenvalue analysis is performed with the use of state-space method and a validation study is conducted by comparing with other undamped plate-oscillator models. The dynamic properties obtained from the proposed model are verified by laboratory tests performed on full-scale lightweight cold-formed steel (CFS) floor systems. The influence of human occupants on the dynamic properties of lightweight steel floors are investigated in three scenarios: an unoccupied floor, a floor with one standing occupant and a floor with two standing occupants. Four human dynamical models in standing position, two with one degree of freedom (SDOF) and others with two degrees of freedom (2-DOF), are adopted in the proposed plate-oscillator model and the obtained results are compared to the test results. Comparisons are also made between the proposed plate-oscillator model with the integrated 2-DOF model for coupled floor-occupant systems. In addition, the need of recalibrating human models for lightweight floor systems is also discussed.